PENGARUH LATIHAN MENENDANG SEMBILAN BOLA KE GAWANG TERHADAP KETERAMPILAN KETEPATAN SHOOTING PEMAIN SSB GALAXY U12 DURI - wujaya, Tony; Ramadi, Ramadi; Zainur, Zainur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is that the accuracy of shooting of SSB Galaxy U-12 Duri is still lacking, it is seen from various test and official match and this is one factor causing the defeat. This type of research is a type of experimental research to see the effect of the form of exercise. The purpose of this riset to see the effect of training kick Nine ball kegawang against the shooting accuracy of SSB Galaxy U12 Duri. The population in this riset is the team SSB Galaxy U12 Duri, amounting to 16 people. Sampling technique is by using total sampling, where the total population is sampled. The data retrieval technique is obtained from pre-test and post test. Instrument in this research use Test shooting at the ball as a tool to measure shooting accuracy skill. The analysis was performed using the t-test. based on data analysis and discussion, it can be concluded that there is a significant influence of training kick Nine ball kegawang against the skills of precision shooting players SSB Galaxy U12 Duri proven with T of 7.609 and Ttabel 1.764. Means Thitung> Tables. At ? = 0,05 level.Keywords: training kick nine balls, precision shooting.